Technical Overview on the Electron Backscattered Diffraction Sample Preparation - Dong-Ik Kim; Byung-Kyu Kim; Ju-Heon Kim (한국현미경학회, 2015)
A technical overview on the various sample preparation methods for electron backscattered diffraction (EBSD) analysis is carried out. The mechanical polishing with colloidal silica f nish, electro-chemical polishing, dual layer coating and ion beam milling are introduced for the common sample preparation methods for EBSD observation and some issues that are frequently neglected by the common EBSD users but should be considered to get a reliable EBSD data are discussed. This overview would be especially helpful to the people who know what EBSD technique is but do not get a reliable EBSD data because of diff culties in sample preparation.